New constraints on tectonism and magmatism from the eastern sector of the Trans-Mexican Volcanic Belt (Chignahuapan Horst, Puebla, México). (December 2021) - Gómez-Alvarez, Fidel; Garduño-Monroy, Víctor Hugo; Sosa-Ceballos, Giovanni; Jiménez-Haro, Adrián; Liotta, Domenico; Gaitan-Ramirez, Maria Felix; Brogi, Andrea; Israde-Alcántara, Isabel; Najera-Blas, Sergio Manuel; Wheeler, Walter; Forster, Marnie; Garcia-Hernández, Oscar Humberto
Abstract: The Quaternary Acoculco (<2.7 my) and Los Humeros (<46 ky) calderas, located in the eastern sector of the Trans-Mexican Volcanic Belt (TMVB), are separated by a regional structure known as the Chignahuapan Horst (ChH). The tectonic and magmatic evolution of the ChH comprises four stages: 1) Upper Cretaceous-Paleocene Laramide orogeny, related to the deformation of sedimentary successions; 2) a sedimentary hiatus followed by the initial stage of the TMVB (Middle Miocene); 3) a Miocene NE-SW oriented extension responsible for the NW-SE normal faults that controlled the volcanic processes and the emplacement of calc-alkaline magmas that formed the Aquixtla sequence; 4) a magmatic hiatus prolonged until 1.6 ± 0.15 my; 5) Pliocene-Quaternary normal faults controlled the emplacement of tholeiitic-transitional magmas and the monogenetic volcanism distribution that formed the Apizaco-Chignahuapan sequence. Coevally to the Miocene NE-SW and Pliocene-Quaternary NW-SE tectonic extensional phases, NE-SW and NW-SE transfer faults were developed. NE-SW normal faults and NW-SE strike-slip faults correspond to fault systems optimally oriented with the current stress field, thus, these faults can be considered as potentially active structures controlling magma emplacement and the distribution of volcanic structures at the surface. Highlights: Tectonism and magmatism in the eastern portion of the Trans-Mexican Volcanic Belt. Characterization of the Miocene-Quaternary faulting stages and volcanic response. Basins development by extensional tectonics, normal and transfer faults associations. Changes in magmatic affinity, volcanism type, and stress field.